Long Digital Extensor Tendon Mineralization and Cranial Cruciate Ligament Rupture in a Dog. Issue 5 (30th January 2014) - Kennedy, Katie C.; Perry, James A.; Duncan, Colleen G.; Duerr, Felix M.
<x xml:space="preserve">Abstract</x> Objective To report clinical and histopathologic features of long digital extensor (LDE) tendon mineralization with concurrent cranial cruciate ligament (CCL) rupture in a dog. Study Design Case report. Animal 1.5‐year‐old, male castrated, English bulldog mix weighing 31.5 kg. Methods Pre‐ and postoperative orthogonal radiographs, arthroscopic evaluation, arthrotomy with en bloc surgical excision, and histopathologic analysis of the excised LDE tendon. Results There was radiographic evidence of mineralization in the region of the proximal LDE and stifle instability suggestive of CCL rupture. Arthroscopy, and subsequent arthrotomy, showed complete tearing of the CCL and an intact but grossly thickened LDE. No evidence of avulsion or bony proliferation associated with the LDE was appreciated. Tibial plateau leveling osteotomy (TPLO) and tenectomy of the LDE returned the dog to normal weight‐bearing. No evidence of ectopic mineralization in the affected limb or similar clinical signs in the contralateral limb have been observed in 12 months follow‐up. Conclusions LDE tenectomy followed by stabilization of the stifle by TPLO resulted in a functional outcome. Mineralization without concurrent avulsion of the LDE has not been reported in dogs; however, posterolateral tendon injury in people has been linked to knee instability and cruciate ligament rupture.